(untitled) (Sociologisk Forskning, 1995)
Inverted goal-rationality. Umensch and Erlebnis-society The article takes its point of departure in a recent attempt at a synthesis in the sociology of culture by Gerhard Schulze. It focuses on the concept of Erlebnis-rationality, i.e. acting aimed at bringing about an intended change of one’s inner subjective state. This concept is related to a fundamental category in Arnold Gehlens anthropology and theory of action: Umkehr der Antriebsrichtung, that I choose to call ”inverted goal-rationality”. Gehlen traces this kind of action - in the form of orgiastic and ascetic ecstasies - back to the beginnings of mankind. Inverted goal-rationality is today a central and wide-spread orientation in the life of Western man - e.g. in the form of consumption for the purpose of having a certain positive Erlebnis. Finally, the article poses the question what it means for a society that an inverted goal-rationality has attained such a central position.